Does a Cryptocurrency Comply with Shariah? Empirical Evidence from ARCH-GARCH Economic Model - Riswanti Budi Sekaringsih; Hasan Al-Banna (Global Review of Islamic Economics and Business, 2022)
The objective of this paper is to analyze the debate about cryptocurrency as money from an Islamic point of view. Money in Islam that is based on urf of custom has also some requirements, such as its stability. Some fatwas in Indonesia regarding the legitimacy of cryptocurrency must be evidenced with an empirical-based. The study used 25 cryptocurrency prices and related information. By employing ARCH and GARCH, the study revealed that cryptocurrency is hugely volatile and, thus, does not fulfill such criterion as money from an Islamic perspective, and is normally used for speculation. Hence, this study suggests that cryptocurrency is still reluctant to be used for a transaction.